2018
DOI: 10.1055/s-0043-124080
|View full text |Cite
|
Sign up to set email alerts
|

Detection of early neoplasia in Barrett’s esophagus using lectin-based near-infrared imaging: an ex vivo study on human tissue

Abstract: Background and study aims  Endoscopic surveillance for Barrett’s esophagus (BE) is limited by long procedure times and sampling error. Near-infrared (NIR) fluorescence imaging minimizes tissue autofluorescence and optical scattering. We assessed the feasibility of a topically applied NIR dye-labeled lectin for the detection of early neoplasia in BE in an ex vivo setting. Methods  Consecutive patients undergoing endoscopic mucosal resection (EMR) for BE-related early neoplasia were recruited. Freshly collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…To truly establish the performance of the color-based classification in a clinically realistic scenario, hyperspectral data should in future be acquired from samples in which a more fine grained histopathological ground truth is available, for example, in mapped endoscopic mucosal resections 18,19 . Once available, the CNN could be more thoroughly tested and also further tailored for application in the discrimination of early cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To truly establish the performance of the color-based classification in a clinically realistic scenario, hyperspectral data should in future be acquired from samples in which a more fine grained histopathological ground truth is available, for example, in mapped endoscopic mucosal resections 18,19 . Once available, the CNN could be more thoroughly tested and also further tailored for application in the discrimination of early cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, molecular CLEM is considered to be a novel method for diagnosis of dysplastic Barrett’s lesions that allows for visualization of cellular processes in real-time by combinations of a variety of either molecular probes or peptides with fluorescent items. Moreover, near-infrared imaging endoscopy with fluorescence lectin was reported to be capable of differentiating neoplastic from non-dysplastic BE lesions [ 116 ]. Nagengast WB et al also reported that near-infrared imaging endoscopy with use of topical and systemic tracers of VEGFA were useful for diagnosis of neoplastic lesions in BE cases, as a higher detection rate was demonstrated as compared to not only WLE but also NBI endoscopy [ 117 ].…”
Section: Endoscopic Findings Showing Possible Predictive Biomarkermentioning
confidence: 99%
“…FME employs fluorescently labeled probes, administered either topically or systemically, and an endoscopic detection system to visualize specific fluorescence in a range not affected by natural autofluorescence (typically in the near‐infrared range). Examples of molecular probes used so far for Barrett's dysplasia include the antivascular endothelial growth factor A (VEGFA) antibody bevacizumab, wheat germ agglutinin, which probes cancer‐related surface glycoprotein, and a synthetic polypeptide ASYNYDA, which likely binds cyclophilin A . These detection modalities have only been validated ex vivo or in very small and selected patient cohorts and will require further studies to prove their potential in Barrett's dysplasia detection.…”
Section: Surveillancementioning
confidence: 99%